2007
DOI: 10.1152/ajpgi.00582.2006
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide disrupts tight junctions in cholangiocyte monolayers by a c-Src-, TLR4-, and LBP-dependent mechanism

Abstract: Bile duct epithelium forms a barrier to the backflow of bile into the liver parenchyma. However, the structure and regulation of the tight junctions in bile duct epithelium is not well understood. In the present study, we evaluated the effect of lipopolysaccharide on tight junction integrity and barrier function in normal rat cholangiocyte monolayers. Lipopolysaccharide disrupts barrier function and increases paracellular permeability in a time- and dose-dependent manner. Lipopolysaccharide induced a redistrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 49 publications
10
105
0
1
Order By: Relevance
“…Until now, the relationship between innate immune response and TJ functions was investigated using intestinal epithelial cells and cholangiocytes (34,35). In intestinal epithelial cells, stimulation with TLR2 ligands led to enhanced TER via PKCa and PKCd activation; however, involvement of atypical PKC had not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the relationship between innate immune response and TJ functions was investigated using intestinal epithelial cells and cholangiocytes (34,35). In intestinal epithelial cells, stimulation with TLR2 ligands led to enhanced TER via PKCa and PKCd activation; however, involvement of atypical PKC had not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, effective delivery of siRNA duplex and exogenous genes into confluent T84 monolayers is difficult to date and is still challenging to those who use T84 monolayers (48) although some researchers have applied siRNA duplexes to subconfluent T84 cells that were grown on plastic (49 -51). One report indicated that siRNA was introduced into 70 -75% confluent rat cholangiocytes that were then trypsinized and seeded onto Transwell supports (52). This approach is problematic in T84 cells because the duration required for T84 cells to reach full confluence and functional differentiation is typically around 7 days, and it is beyond the time frame for studying functions of protein kinases by knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of Trans-epithelial Electrical Resistance (TEER)-TEER was measured using Millicell electrical resistance system (Millipore) as reported (14,26) and expressed as ohms/ cm 2 , where ohm is the observed value of resistance, and cm 2 is the surface area of the membrane. The background resistance of the trans-well membrane (ϳ30 ohms/cm 2 ) was subtracted from the observed resistance values.…”
Section: Cell Culture and Whi-p131 Treatment-ht-29mentioning
confidence: 99%